Antiviral Activity of Type I, II, and III Interferons Counterbalances ACE2 Inducibility and Restricts SARS-CoV-2 - Idoia Busnadiego (American Society for Microbiology, 2020)
ABSTRACT Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the cause of coronavirus disease 2019 (COVID-19), is a recently emerged respiratory coronavirus that has infected >23 million people worldwide with >800,000 deaths. Few COVID-19 therapeutics are available, and the basis for severe infections is poorly understood. Here, we investigated properties of type I (β), II (γ), and III (λ1) interferons (IFNs), potent immune cytokines that are normally produced during infection and that upregulate IFN-stimulated gene (ISG) effectors to limit virus replication. IFNs are already in clinical trials to treat COVID-19. However, recent studies highlight the potential for IFNs to enhance expression of host angiotensin-converting enzyme 2 (ACE2), suggesting that IFN therapy or natural coinfections could exacerbate COVID-19 by upregulating this critical virus entry receptor. Using a cell line model, we found that beta interferon (IFN-β) strongly upregulated expression of canonical antiviral ISGs, as well as ACE2 at the mRNA and cell surface protein levels. Strikingly, IFN-λ1 upregulated antiviral ISGs, but ACE2 mRNA was only marginally elevated and did not lead to detectably increased ACE2 protein at the cell surface. IFN-γ induced the weakest ISG response but clearly enhanced surface expression of ACE2. Importantly, all IFN types inhibited SARS-CoV-2 replication in a dose-dependent manner, and IFN-β and IFN-λ1 exhibited potent antiviral activity in primary human bronchial epithelial cells. Our data imply that type-specific mechanisms or kinetics shape IFN-enhanced ACE2 transcript and cell surface levels but that the antiviral action of IFNs against SARS-CoV-2 counterbalances any proviral effects of ACE2 induction. These insights should aid in evaluating the benefits of specific IFNs, particularly IFN-λ, as repurposed therapeutics. IMPORTANCE Repurposing existing, clinically approved, antiviral drugs as COVID-19 therapeutics is a rapid way to help combat the SARS-CoV-2 pandemic. Interferons (IFNs) usually form part of the body’s natural innate immune defenses against viruses, and they have been used with partial success to treat previous new viral threats, such as HIV, hepatitis C virus, and Ebola virus. Nevertheless, IFNs can have undesirable side effects, and recent reports indicate that IFNs upregulate the expression of host ACE2 (a critical entry receptor for SARS-CoV-2), raising the possibility that IFN treatments could exacerbate COVID-19. Here, we studied the antiviral- and ACE2-inducing properties of different IFN types in both a human lung cell line model and primary human bronchial epithelial cells. We observed differences between IFNs with respect to their induction of antiviral genes and abilities to enhance the cell surface expression of ACE2. Nevertheless, all the IFNs limited SARS-CoV-2 replication, suggesting that their antiviral actions can counterbalance increased ACE2.